Penerapan Media Terarium untuk Meningkatkan Kreativitas, Literasi Keuangan, dan Jiwa Kewirausahaan Siswa dalam Program Projek Penguatan Profil Pelajar Pancasila - Minarti, Ipah Budi; Wicaksono, Azizul Ghofar Candra; Amiruddin, Muhammad; Nurwahyunani, Atip (Perkumpulan Kualitama Edukatika Indonesia, 2025)
Terrarium-based project learning is a strategic innovation to support the Pancasila Student Profile Strengthening Project (P5) at MA Roudlotul Mubtadiin. This activity aims to improve students' creativity, financial literacy, and entrepreneurial spirit. Through training, simulation, and hands-on practice methods, students were trained to create and market terrarium products as educational media and economic commodities. Data analysis shows that students have an average creative self-efficacy score of 3.83, financial literacy of 3.85, and entrepreneurship of 3.88 with no significant gender differences. These results indicate the effectiveness of the terrarium approach in shaping independent, creative, and entrepreneurial student profiles. Character education and 21st-century skills can be strengthened through this approach.